2006
DOI: 10.1159/000095760
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Health-Related Quality of Life and Perceived Burden of Informal Caregivers of Individuals with Alzheimer’s Disease

Abstract: This study assessed the impact on health-related quality of life (HRQL) and the perceived burden of informal caregivers of individuals with Alzheimer’s disease (AD) on the Canary Islands (Spain). We utilized a multicenter, cross-sectional design, based on questionnaire responses of 237 informal caregivers of AD patients. Patients were classified according to the degree of severity utilizing the Clinical Dementia Rating Scale. Sociodemographic, HRQL (EQ-5D) and functional dependency data were gathered together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
139
4
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 62 publications
16
139
4
3
Order By: Relevance
“…These results are consistent with a report [30] that older age of family caregivers is associated with poorer overall HRQoL. Whether the age of family caregivers has different effects on their mental and physical health-related outcomes will need to be further explored.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with a report [30] that older age of family caregivers is associated with poorer overall HRQoL. Whether the age of family caregivers has different effects on their mental and physical health-related outcomes will need to be further explored.…”
Section: Discussionsupporting
confidence: 91%
“…These confounders were selected a priori based on previous studies regarding home care and caregiver burden. 12,13 Multivariable logistic regression analysis was employed to examine the relationship between violent patient behavior and bodily pain experienced by caregivers, with adjustment for caregiver burden assessed using Burden Index of Caregivers and the potential confounders described above. In this model, the Burden Index of Caregivers was recoded by tertiles.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Caregiver burden was originally defined by Zarit as the extent to which caregivers perceive that their emotional or physical health, social life, and financial status are suffering as a result of caring for their charges. 9,10 Several studies reveal a relationship between caregiver burden and the characteristics of patients with various diseases, 11,12 such as severe cognitive impairment. 13 In addition to caregiver burden, caregivers subjected to violent patient behavior may experience increased pain.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report that adult children show the highest levels of burden (Coen et al, 2002;Andrén and Elmståhl, 2007;Molyneux et al, 2008), whereas other state that the greatest burden is that experienced by spouse caregivers (Montgomery and Kosloski, 1994;Rinaldi et al, 2005;Serrano-Aguilar et al, 2006). Conversely, some authors have found no significant differences overall (Ferrario et al, 2003;Ankri et al, 2005;Turró-Garriga et al, 2008).…”
Section: Empirical Researchmentioning
confidence: 99%